HUMAN ERROR REDUCTION PROGRAM THROUGH CANONICAL ACTION RESEARCH (CAR) IN WAFER FABRICATION MANUFACTURING FACILITY (Journal of Technology and Operations Management, 2019)
In a wafer fabrication manufacturing facility, thousands of wafers are being processed daily. To manufacture the product, the wafers need to go thru hundreds of steps according to the technologies required. The cycle time to complete a standard product ranges from few weeks to few months, depends on the complexity of the technologies. Due to the difficulty and the complexity of the product, Computer Integrated Manufacturing system (CIM), is widely used as a manufacturing platform. As such, all the processes, equipment and wafers are fully integrated. Nevertheless, not all processes could be processed automatically. In the situation of the halfway processes wafer due to equipment or facility interruption, the wafer, need to be processed manually. Engineers or technicians will manually process the affected wafer according to the specification. The problem arises when; there is a human involvement that ends up with wafers misprocess. The potential revenue lost due to wafer misprocess is vast. Hence, this paper aims to discuss issues related to human error in manufacturing, specifically in Wafer Fabrication Manufacturing Facility. The paper presents partial input for the Canonical Action Research (CAR) that presently being exercised in order to minimize human error by developing a Small Group Activities (SGA) in the manufacturing facility.